An alternative approach to Cigler’s q-Lucas polynomials - Belbachir, Hacène; Benmezai, Athmane (Applied mathematics and computation, 2014)
We modify Cigler’s approach to q-Fibonacci and q-Lucas polynomials by introducing two kinds of q-Lucas polynomials. This allows some new generalizations of classical identities related to Fibonacci and Lucas numbers.